2008
DOI: 10.1002/ajhb.20770
|View full text |Cite
|
Sign up to set email alerts
|

Secular changes in stature and body mass index for Chinese youth in sixteen major cities, 1950s–2005

Abstract: Evidence shows a secular trend in physical growth in China in recent years. We analyze the secular trend of stature and body mass index (BMI) for the period 1950s-2005 to provide biological evidence for policy-makers to identify measures for improving Chinese children's health. Data come from the historical records in 1950s and the successive cycles of the Chinese National Survey on Student's Constitution and Health. Subjects were 7- to 18-year-old youth from 16 cities. Sex-age differences in mean stature and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 33 publications
2
37
0
2
Order By: Relevance
“…The increase in BMI seen in the current study is consistent with the global trend across the second half of the 20th century [9][10][11]. An earlier study of 6-12 year-old Japanese children measured in 1989 and also in 2001/02 reported a rapid increase of children with a BMI above the age-and gender-specific 95th percentile cut-off point [20].…”
Section: Discussionsupporting
confidence: 77%
“…The increase in BMI seen in the current study is consistent with the global trend across the second half of the 20th century [9][10][11]. An earlier study of 6-12 year-old Japanese children measured in 1989 and also in 2001/02 reported a rapid increase of children with a BMI above the age-and gender-specific 95th percentile cut-off point [20].…”
Section: Discussionsupporting
confidence: 77%
“…On a more positive note, some reversed changes in the female adolescents in groups VII and VIII are noticed ( Table 3). Because of the secular growth trend in the meantime, with a faster increase in height than weight, the BMI temporarily decreased, especially in females [28]. V) Since 2000, the prevalence in combined overweightobesity category in the male children in groups I and IV appears to approach the average level of the developed countries, though that of obesity (especially for adolescent girls) remained much lower [29].…”
Section: No Significant Changes In Prevalence Occurred In Other Ruralmentioning
confidence: 94%
“…This has been accompanied by a positive trend in the physical growth of children. 33 An empirical division of China's economic development into stages based on the time cycle of China growth surveys facilitates the analysis of its association with trends in children's growth. In Stage I (before 1975) -out of scope of this analysis -a previous subtle upward trend in growth ceased and even reversed owing to the detrimental effects of famine.…”
Section: The Economic Transitionmentioning
confidence: 99%
“…8 The areas were categorized from highest to lowest economic status as large coastal cities, high, medium or low cities, high, medium or low rural areas and poor western rural areas.…”
Section: Growth and Nutrition Datamentioning
confidence: 99%
See 1 more Smart Citation